2021
DOI: 10.1113/ep089356
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic changes in the acute hyperkalaemia produced by intragastric KCl load in rats

Abstract: A variety of animal models have been proposed to study hyperkalaemia, but most of them have meaningful limitations when the goal is to study the effect of potassium overload on healthy kidneys. In this study, we aimed to introduce a new approach for induction of hyperkalaemia in a reliable and reproducible animal model. We used intragastric administration of potassium chloride [KCl 2.3 M, 10 ml/(kg body weight)] to male Holtzman rats (300-350 g) to induce hyperkalaemia. The results showed that this potassium l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…To determine the high end of endogenous production, we adapted a human protocol that combined dietary sodium deprivation with potassium supplementation, followed by acute potassium infusion (55). Supplementing dietary potassium in sodium-deprived mice, followed by potassium gavage (56), produced higher concentrations of endogenous aldosterone in blood plasma (ranging 313 to 990 ng/dL, Figure 5A ) and in CSF (ranging 48 to 74 ng/dL, Figure 5B ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the high end of endogenous production, we adapted a human protocol that combined dietary sodium deprivation with potassium supplementation, followed by acute potassium infusion (55). Supplementing dietary potassium in sodium-deprived mice, followed by potassium gavage (56), produced higher concentrations of endogenous aldosterone in blood plasma (ranging 313 to 990 ng/dL, Figure 5A ) and in CSF (ranging 48 to 74 ng/dL, Figure 5B ).…”
Section: Resultsmentioning
confidence: 99%
“…For dietary sodium deprivation plus potassium supplementation, we modeled our approach after a similar dietary protocol followed by acute infusion of potassium chloride (KCl) in human subjects (55). However, instead of intravenous infusion at the end of our protocol, we gave a bolus of potassium by gavage (3M KCl, 0.1 mL per 10 g), similar to previous rodent experiments (56). Also, after pilot experiments testing a range of concentrations, we found that mice show no aversion to 1.5% or less KCl in drinking water (they consumed this solution at the same daily volumes as dH 2 O).…”
Section: Methodsmentioning
confidence: 99%
“…However, the optimal levels of high serum (K + ) and the standard of optimal levels are undefined. Potassium (K + ) is among the most abundant cations in cells, which can cause alterations in the resting membrane potential, nerve and muscle excitability, and cardiac electrical activity [ 46 ]. Elevated serum (K + ) leads to changes in the electrical activity of the heart, which are reflected in the ECG and changes in the ECG can provide crucial insights into myocardial function in turn [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…As serum (K + ) levels continue to increase, it can lead to heart block, asystole and ventricular tachycardia (VT)/ventricular fibrillation (VF), and a significant decrease in MAP. In contrast to humans, the rats failed to observe significant “high and sharp” T-waves on the ECG during the increased serum (K + ) levels but were able to observe complete changes in the P waves and QRS complexes [ 46 ]. Therefore, we selected the P and QRS waves with significant changes as the grouping criteria: a decrease in P wave amplitude to 1/2 the basal value was used as the low-dose group (P group), and a widening of the QRS complex to three times the basal value was used as the high-dose group (Q group).…”
Section: Discussionmentioning
confidence: 99%